2019
DOI: 10.1002/aoc.5195
|View full text |Cite
|
Sign up to set email alerts
|

Commercial drug norfloxacin as a novel ligand for the copper‐catalyzed N‐arylation of imidazole with aryl halides

Abstract: Norfloxacin was used as an efficient ligand for the CuBr-catalyzed C-N coupling reaction of imidazole and aryl halides. The protocol presented good functional group compatibility, permitting many aryl halides to react with imidazole to form the desired products in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Based on the results and reported literatures, [ 27,28 ] the reaction mechanism was proposed (Scheme 4). Initially, the combination of vitamin C/glycerol changed CuO to Cu I L via vitamin C coordinating with CuO, which reacted with ArX to form the intermediate i via oxidative addition.…”
Section: Resultsmentioning
confidence: 97%
“…Based on the results and reported literatures, [ 27,28 ] the reaction mechanism was proposed (Scheme 4). Initially, the combination of vitamin C/glycerol changed CuO to Cu I L via vitamin C coordinating with CuO, which reacted with ArX to form the intermediate i via oxidative addition.…”
Section: Resultsmentioning
confidence: 97%
“…[ 7 ] Generally speaking, single copper served as the catalyst is not active, but adding ligand to copper catalyst can enhance the catalytic efficiency. [ 8 ] In view of the significance of the ligand, diverse ones have been developed, such as, 2‐carbomethoxy‐3‐hydroxyquinoxaline‐di‐ N ‐oxide, [ 9 ] β ‐keto ester, [ 10 ] 2‐pyridin‐2‐yl‐1 H ‐benzoimidazole, [ 11 ] norfloxacin, [ 12 ] 2,2′‐biimidazole, [ 13 ] 1,1,1‐tris (hydroxymethyl)ethane, [ 14 ] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Xie et al reported that norfloxacin as a ligand can promote the coupling reaction of aryl iodides and imidazole at 120 1C. 7 Therefore, we tested eight commercially available quinolone drugs for copper-catalyzed coupling reactions. The results showed that there was a stronger effect from ciprofloxacin hydrochloride than from that of other quinolone drugs.…”
mentioning
confidence: 99%